Therapies for RYR1-Related Myopathies: Where We Stand and the Perspectives - Beaufils, Mathilde; Travard, Lauriane; Rendu, John; Marty, Isabelle (Current Pharmaceutical Design, 2022)
RyR1-related myopathies are a family of genetic neuromuscular diseases due to mutations in the RYR1 gene. No treatment exists for any of these myopathies today, which could change in the coming years with the growing number of studies dedicated to the pre-clinical assessment of various approaches, from pharmacological to gene therapy strategies, using the numerous models developed up to now. In addition, the first clinical trials for these rare diseases have just been completed or are being launched. We review the most recent results obtained for the treatment of RyR1-related myopathies, and, in view of the progress in therapeutic development for other myopathies, we discuss the possible future therapeutic perspectives for RyR1-related myopathies.
Keywords: gene therapy